The Use of a Bio-Inductive Collagen Patch to Supplement Repair of Large and Massive Rotator Cuff Tears Including Revisions: Clinical and Radiographic Outcomes at 2-year Follow Up. Issue 7 (30th July 2018) - Thon, Stephen; O'Malley, Lawrence K.; O'Brien, Michael John; Savoie, Felix H.
Objectives: Failures of large, massive, and revision rotator cuff repairs is a challenging problem within orthopedics. Poor tendon tissue and vascularity are known causes for failure of rotator cuff repairs. The purpose of this study was to assess the outcomes and healing rates when large and massive rotator cuff repairs are augmented with a bio-inductive collagen scaffold patch. Methods: Twenty-three patients undergoing repair of large (two tendon) or massive (three tendon) rotator cuff tears augmented with a bio-inductive collagen patch were followed prospectively for 2 years. Postoperative ultrasound (US) assessed tendon thickness at 3, 6, 12, and 24 months. MRI was utilized to confirm healing and tendon thickness at least 6 months post-operatively. Results: 16 of 23 patients had previous failed rotator cuff repairs. Eleven patients had large rotator cuff tears while twelve patients had massive rotator cuff tears. 21 of 23 patients successfully healed their rotator cuff repairs and new tissue formation was appreciated in all 23 patients. Ultrasound rotator cuff thickness ranged from 4.5-9mm at most recent follow-up. Overall, a 91% (21/23) success rate was confirmed on US and MRI. Conclusion: Clear indications for the use of this bio-inductive collagen scaffold have yet to be established. Our results show that it may have utility in improving the healing rates of large and massive rotator cuff repairs. New tendon formation was apparent on both US and MRI with relatively high healing rates at two years. While these early results are promising, long term-follow up is needed to identify the proper indications for its use. Level of Evidence: Level IV - Case series.